Assessment Of Witness Testimonials As Evidence In Civil Cases - Paulus Tiku Taru Padang (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to investigate and explain the judge's judgment of witness testimony as evidence in the judge's decision. The study employed a normative legal research technique with primary legal sources. In accordance to the author, this judge's reasoning is incorrect due to the fact that there is an oral agreement between the plaintiff and the defendant, which is confirmed by testimony from witnesses and expert witnesses, it cannot be classified as a breach of contract because it does not meet the requirements set forth in Article 58 of the Indonesian Civil Code. The rules and regulations of Article 58 of the Indonesian Civil Code are coercive legal provisions (dwingend recht). Article 58 of the Indonesian Civil Code contains three conditions: 1. The vows of marriage must be registered in the civil registry; 2. Civil registration officials must declare the marriage plans on the notice board; and 3. Claims/lawsuits must be filed within 18 months of the marriage announcement. The judge's assessment that the defendant had broken his vow was incorrect. As a result, the participation of the witness in providing information in collaboration with other witnesses cannot be used to prove the marriage commitment.